2018
DOI: 10.1590/1678-4499.2017285
|View full text |Cite
|
Sign up to set email alerts
|

Plant spatial arrangement affects grain production from branches and stem of soybean cultivars

Abstract: Phenotypic plasticity is the ability of plants to undergo changes in morphology and yield components to adapt themselves to distinct environmental conditions. The knowledge on the changes in yield components of branches and stems at varied plant spatial arrangements needs to be updated due to recent changes in soybean production system. Thus, this study aimed to evaluate the yield components of branches and stems, as well as to assess the share of these plant parts in the total grain yield of soybean cultivars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 23 publications
1
7
0
6
Order By: Relevance
“…The single plant biomass was the highest in 2017, the SPlY in both years and single pod grain yield in 2017. Similar to Ferreira et al (2018), who reported a higher production of pods and grains in branches with narrower row spacing, we also observed more pods plant -1 and more grains plant -1 with wider row spacings. Contrary to our observations, Cox and Cherney (2011) reported for three row spacings (19, 38 and 76 cm) no differences in the plant density but a lower AGDM and grain yield with wider row spacing due to a lower pod density, a lower grain density and a lower number of grains plant -1 , whereas grains pod -1 increased as also observed in our study with wider row spacing.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The single plant biomass was the highest in 2017, the SPlY in both years and single pod grain yield in 2017. Similar to Ferreira et al (2018), who reported a higher production of pods and grains in branches with narrower row spacing, we also observed more pods plant -1 and more grains plant -1 with wider row spacings. Contrary to our observations, Cox and Cherney (2011) reported for three row spacings (19, 38 and 76 cm) no differences in the plant density but a lower AGDM and grain yield with wider row spacing due to a lower pod density, a lower grain density and a lower number of grains plant -1 , whereas grains pod -1 increased as also observed in our study with wider row spacing.…”
Section: Discussionsupporting
confidence: 89%
“…Contrary to that, Envi (1973) observed a decrease of the TKW of side branches with increasing seeding rate. Ferreira et al (2018) reported that with increasing seeding rate, the number of pods plant -1 was reduced in a greater magnitude at the branches than at the main stem whereas grain pod -1 was neither altered in the pods located at the stem or at the branches when the plant arrangement changed. Similar to these observations for soybean, also in faba bean, different plant densities tended not to affect the pod density (Patrick and Stoddard, 2010), as competition between plants generally reduced pods plant -1 rather than grains pod -1 or seed size (Adisarwanto and Knight, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low proportion of branches in grain production for plants grown at higher sowing densities is probably due to the rapid closing of the canopy during vegetative growth, leading to an unfavorable environment to branching. Thus, production becomes more dependent on the stems (Ferreira et al, 2018).…”
Section: /9mentioning
confidence: 99%
“…Soybean plants at low densities tend to emit a high number of branches and increase their size, providing an increase in the number of pods per plant, which generates higher production per plant, thus maintaining the crop grain yield, even with a reduction in the number of plants per area (Ferreira et al, 2018). High plant densities and small interrow spacings decrease the contribution of branches to grain yield, increasing the proportion of stems in the production.…”
Section: Introductionmentioning
confidence: 99%